2018
DOI: 10.3389/fpls.2018.01895
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Wall Regulating NACs Differentially Bind at the Promoter at a CELLULOSE SYNTHASE A4 Cis-eQTL

Abstract: Arabidopsis thaliana CELLULOSE SYNTHASE A4/7/8 (CESA4/7/8) are three non-redundant subunits of the secondary cell wall cellulose synthase complex. Transcript abundance of these genes can vary among genotypes and expression quantitative trait loci (eQTL) were identified in a recombinant population of the accessions Bay-0 and Shahdara. Genetic mapping and analysis of the transcript levels of CESAs between two distinct near isogenic lines (NILs) confirmed a change in CESA4 expression that segregates within that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
(104 reference statements)
2
9
0
Order By: Relevance
“…These include the VNS, W-box, and Dof binding motif. The VNS motif featured heavily in secondary cell wall development, and is a consensus sequence bound by the VND, NST, and SND NAC transcription factors (Olins et al, 2018). Consistent with our observation of rhythmic secondary cell wall genes, this motif was enriched in both diurnal and constant conditions.…”
Section: Researchsupporting
confidence: 88%
See 1 more Smart Citation
“…These include the VNS, W-box, and Dof binding motif. The VNS motif featured heavily in secondary cell wall development, and is a consensus sequence bound by the VND, NST, and SND NAC transcription factors (Olins et al, 2018). Consistent with our observation of rhythmic secondary cell wall genes, this motif was enriched in both diurnal and constant conditions.…”
Section: Researchsupporting
confidence: 88%
“…We identified 291 (out of 477 total DAP-seq motifs) significantly enriched motifs, including the core diurnal elements EE, GATA, TBX and G-box (Figs 9, S13). In contrast to ELEMENT, this approach enabled us to identify larger, split elements like VNS (VND/NST/SND: CTTNNNNNNAAG) (Olins et al, 2018), which was enriched in constant conditions and thermocycles, suggesting that it is very likely part of circadian clock regulation. In addition, we observed enrichment for the CACT motif in the morning in LDHC and LDHH.…”
Section: Researchmentioning
confidence: 99%
“…The same promoters that interact with the secondary cell wall regulating MYB transcription factors often interact with NAC transcription factors, collectively referred to as the SECONDARY WALL NACs (SWN) or the VND, NST/SND, SMB related (VNS) (Ohtani et al, 2011;Zhong et al, 2011). This group of proteins is generally classified into four clades, all binding the similarly named VNS element in in vitro assays (O'Malley et al, 2016;Olins et al, 2018), which is consistent with independently identified TERE and SNBE binding sites for the same proteins (Pyo et al, 2007;Valdivia et al, 2013). In A. thaliana, three of the clades that include the VASCULAR-RELATED NAC-DOMAINs (VNDs), activate cell wall thickening directly and by activating the previously described downstream MYBs (Kubo et al, 2005).…”
Section: Transcriptional Regulation Of Secondary Cell Wall Thickementioning
confidence: 99%
“…10) . In contrast to ELEMENT, This approach enabled us to identify larger, split elements like VNS (VND/NST/SND, CTTNNNNNNAAG, (Olins et al , 2018) ), which was enriched in constant conditions and thermocycles, suggesting that it is very likely part of circadian clock regulation. In addition, we observed enrichment for the CACT motif in the morning in LDHC and LDHH.…”
Section: Time-of-day Specific Cis -Regulatory Sequencesmentioning
confidence: 99%
“…Light-dependent photoreceptor activity, in turn, influences the function of core clock proteins. In the dark, ZTL targets TOC1, PRR5, and CCA1 HIKING EXPEDITION (CHE) proteins for degradation, releasing the repression of the morning-expressed genes, CCA1 and LHY (Más et al , 2003;Lee et al , 2018) . Both cryptochrome and phytochrome activities have been implicated in controlling the morning loop function of PRR7 and PRR9 (Farré et al , 2005) .…”
Section: Introductionmentioning
confidence: 99%